ENT300 Fresh Clean Laundry / Edwina Anak Lingking... [et.al] - Lingking, Edwina; Bujang, Gracilla Claresa; Morshidi, Siti Fatimah; Ahim, Abdul Hafiz; Bueh, Jeffery (2011)
The name of our company is Fresh Clean Laundry. The business is in form of enterprise which consists of five members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is laundry which our concepts are collect and deliver from home to home. We do operate the walk-in self service laundry and it give the customer more option either to use our facilities to wash their own clothes or they leave it to us to wash it. We also operate kiosk which becomes the place for the customer to have their beverages and at the same time they wait for their clothes. These concepts are established due to the modern contemporary style of living which the people in this global era become busier with their work and may not be able to do some house chores such as cleaning their own clothes. Our concept is also accurate and suitable with the campus way of life which the student’s time nowadays become more compact and it also suitable for the working people that do not have their time in doing their laundry. Our business operation on Monday to Saturday on 9 a.m until 9 p.m and in Sunday we open on 10 a.m until 5 p.m. Our laundry delivery is on Monday and Thursday.